Cover Feature: Enhancing Ligand‐Free Fe‐Catalyzed Aminocarbonylation of Alkynes by ZrF4 (ChemCatChem 21/2019). Issue 21 (24th October 2019) - Huang, Zijun; Dong, Yanan; Li, Yudong; Makha, Mohamed; Li, Yuehui
Abstract : The Cover Feature illustrates ligand‐free Fe‐catalyzed aminocarbonylation of alkynes by ZrF4 . In their Communication, Z. Huang et al. demonstrated the utility of readily prepared ZrF4 in transforming various aromatic and aliphatic alkynes into the desired α, β ‐unsaturated amides in good to excellent yields. Preliminary mechanistic studies by in‐situ NMR experiments provided insights into the catalytic role of ZrF4 through F⋅⋅⋅H‐N hydrogen bonding and activation of Fe3 (CO)12 . More information can be found in the Communication by Z. Huang et al. on page 5236 in Issue 21, 2019 (DOI: 10.1002/cctc.201900995 ).